2003
DOI: 10.1081/ncn-120021426
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (Z)-(2,3-bis-Hydroxymethyl)methylenecyclopropane Analogues of Purine Nucleosides

Abstract: Synthesis of (Z)-(2,3-bis-hydroxymethyl)methylenecyclopropane analogues of nucleosides adenosine 10a, 10b, 10c and 17 is described. Epimerization of Feist's acid (11) using acetic anhydride gave cyclic anhydride 12 which was reduced in situ to give diol 13. Acetylation (compound 14) followed by addition of bromine led to dibromo derivative 15. Alkylation-elimination of adenine with 15 afforded, after deacetylation, analogue 10a. Similar treatment of 2-amino-6-chloropurine and 2,6-diaminopurine led to diacetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This fact was more recently confirmed by several authors, who have performed the reduction of carboxyl functionalities directly linked to the cyclopropane ring of various methylene-and alkylidenecyclopropanes by using LiAlH 4 , [75,121] or DIBAL [45,46,55,57] as the reducing agent. This compatibility was well illustrated by the development of a new synthesis of the antiviral agent synguanol, which involved as the last step a DIBAL-mediated reduction of a guanine methylenecyclopropane ester.…”
Section: Functionalizations Away From the Methylenecyclopropane Moietymentioning
confidence: 61%
See 1 more Smart Citation
“…This fact was more recently confirmed by several authors, who have performed the reduction of carboxyl functionalities directly linked to the cyclopropane ring of various methylene-and alkylidenecyclopropanes by using LiAlH 4 , [75,121] or DIBAL [45,46,55,57] as the reducing agent. This compatibility was well illustrated by the development of a new synthesis of the antiviral agent synguanol, which involved as the last step a DIBAL-mediated reduction of a guanine methylenecyclopropane ester.…”
Section: Functionalizations Away From the Methylenecyclopropane Moietymentioning
confidence: 61%
“…In order to delineate the structure-activity relationships of this class of antiviral nucleoside analogues, a series of (Z)-(2,3-bis-hydroxymethyl)-methylenecyclopropane analogues of purine derivatives could be successfully synthesized in good yields on the basis of the reaction of (E,Z)-1-bromo-1-bromomethyl-2,3-bis(acetoxymethyl)cyclopropane in the presence of Cs 2 CO 3 and a base, such as adenine, 2-amino-6-chloropurine, guanine or 2,6-diaminopurine (Table 1, entries 13-16). [55] The alkylationelimination methodology was also applied to the synthesis of 2,2,3-tris(hydroxymethyl)methylenecyclopropane analogues of nucleosides but, however, none of these novel products exhibited a significant antiviral activity. [56] Moreover, a mixture of chiral Z-and E-isomers of (1,2-dihydroxyethyl)methylenecyclopropane analogues of 2'-deoxyadenosine or 2'-deoxyguanosine were synthesized by reaction of a mixture of (R)-1-[(1S,2R)-2-bromo-2-(bromomethyl)cyclopropyl]-ethane-1,2-diyl diacetate and (R)-1-[(1S,2S)-2-bromo-2-(bromomethyl)cyclopropyl]ethane-1,2-diyl diacetate with adenine or 2-amino-6-chloropurine, in 56-57% yield, respectively, followed by deacetylation (Table 1, entries 17 and 18).…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…In the past, it has been demonstrated that the use of powerful oxidizing systems such as oxalyl chloride in DMSO,57 as well as reducing systems, was generally compatible with the presence of cyclopropylidene functionalities. This fact was more recently confirmed by several authors, who have performed the reduction of carboxyl functionalities directly linked to the cyclopropane ring of various methylene‐ and alkylidenecyclopropanes by using LiAlH 4 ,75,121 or DIBAL45,46,55,57 as the reducing agent. This compatibility was well illustrated by the development of a new synthesis of the antiviral agent synguanol, which involved as the last step a DIBAL‐mediated reduction of a guanine methylenecyclopropane ester 46.…”
Section: From Preformed Methylene‐ and Alkylidenecyclopropanesmentioning
confidence: 62%
“…After a subsequent debenzylation, the corresponding Z ‐ and E ‐alcohols were demonstrated to be moderate substrates for adenosine deaminase. In order to delineate the structure‐activity relationships of this class of antiviral nucleoside analogues, a series of ( Z )‐(2,3‐bis‐hydroxymethyl)‐methylenecyclopropane analogues of purine derivatives could be successfully synthesized in good yields on the basis of the reaction of ( E,Z )‐1‐bromo‐1‐bromomethyl‐2,3‐bis(acetoxymethyl)cyclopropane in the presence of Cs 2 CO 3 and a base, such as adenine, 2‐amino‐6‐chloropurine, guanine or 2,6‐diaminopurine (Table 1, entries 13–16) 55. The alkylation–elimination methodology was also applied to the synthesis of 2,2,3‐tris(hydroxymethyl)methylenecyclopropane analogues of nucleosides but, however, none of these novel products exhibited a significant antiviral activity 56.…”
Section: From Preformed Cyclopropanesmentioning
confidence: 99%